Conservation Policies, Eco-Tourism, and End of Pastoralism in Indian Himalaya? - Singh, Rashmi; Sharma, Rishi Kumar; Bhutia, Tsering Uden; Bhutia, Kinzong; Babu, Suresh (Frontiers in Sustainable Food Systems, 2021)
State-led policies of pastoralist removal from protected areas, following the fortress model of biodiversity conservation, have been a common practice across parts of Asia and Africa. In the Himalayan region of South Asia, restrictive access and removal of pastoralist communities from protected areas have been compensated by the state through “eco”-tourism. In this paper, we critique the current conservation model adopted in the Indian Himalaya, which focuses on a conservation-pastoral eviction-ecotourism coupling. With a focus on pastoralists and pastoral practices, we argue that this model is neither an inclusive engine of development, nor does it always help conservation. Instead, it recreates a landscape favoring the state's interests, produces exclusions, and may also negatively affect both society and ecology. We build on the case of Khangchendzonga National Park (KNP) situated in Sikkim, Eastern Himalaya. We used mixed methods and conducted 48 semi-structured interviews, 10 key informant interviews, and two focused group discussion in the four village clusters situated in the vicinity of KNP, West Sikkim. The grazing ban policy and concomitant promotion of tourism caused the end of pastoralism in KNP. It transformed a pastoral cultural landscape into a tourist spot with a transition in livestock from the traditional herds of yak and sheep to the pack animals and non-native hybrid cattle. Locally perceived social impacts of the grazing ban include loss of pastoral culture, economic loss, and the exclusion of the pastoral community from the park. As per the respondents, perceived ecological effects include a decline in vegetation diversity in the high-altitude summer pastures, altered vegetation composition in the winter due to plantation of non-native tree species, and increased incidents of human-wildlife conflict. Rangelands of the Himalaya transcend political boundaries across countries. The conservation model in Himalaya, should henceforth be done with a trans-boundary level planning involving the prime users of high-altitude rangelands, i.e., the pastoralists. The lessons from this study can help design effective future policy interventions in landscapes critical for both pastoralist cultures and wildlife conservation.